NARATOR SEBAGAI PENYAMPAI KRITIK SOSIAL DALAM NOVEL MOHA LE FOU MOHA LE SAGE KARYA TAHAR BEN JELLOUN - Intan, Tania (JURNAL ILMU BUDAYA, 2018)
In each literary work, the author through the narrator conveys his ideas or criticisms of an issue that is the inspiration of his writing. A novel in French, Moha le Fou Moha le Sage (MFMS) by Tahar ben Jelloun, illustrates the delivery of certain ideas and criticisms with the social background of the newly independent Maghreb state from French colonization. This research was made to describe the conditions that were criticized and the way the narrator expressed his criticism. The sociology of literature approach is used, to study the object of the novel MFMS research. Data was collected by reading and recording techniques, and analyzed using descriptive analytic techniques. The results show that the criticized conditions in this novel relate to a very sharp dichotomy in social configuration, between strong and weak, male and female, employer and slave, white and black, educated and not. The narrator, Moha, speaks as himself to convey the plight of the weak that are unable or prevented from speaking up. He gives advice, reprimands, reminds, threatens, and persuades him to be heard. But all his efforts were in vain because people were generally too busy looking for money and were reluctant to stop listening to other people's complaints.